Health outcomes of youth development programme in England: prospective matched comparison study. (7th July 2009) - Wiggins, Meg; Bonell, Chris; Sawtell, Mary; Austerberry, Helen; Burchett, Helen; Allen, Elizabeth; Strange, Vicki
Abstract : Objective To evaluate the effectiveness of youth development in reducing teenage pregnancy, substance use, and other outcomes. Design Prospective matched comparison study. Setting 54 youth service sites in England. Participants Young people (n=2724) aged 13-15 years at baseline deemed by professionals as at risk of teenage pregnancy, substance misuse, or school exclusion or to be vulnerable. Intervention Intensive, multicomponent youth development programme including sex and drugs education (Young People's Development Programme) versus standard youth provision. Main outcome measures Various, including pregnancy, weekly cannabis use, and monthly drunkenness at 18 months. Results Young women in the intervention group more commonly reported pregnancy than did those in the comparison group (16% v 6%; adjusted odds ratio 3.55, 95% confidence interval 1.32 to 9.50). Young women in the intervention group also more commonly reported early heterosexual experience (58% v 33%; adjusted odds ratio 2.53, 1.09 to 5.92) and expectation of teenage parenthood (34% v 24%; 1.61, 1.07 to 2.43). Conclusions No evidence was found that the intervention was effective in delaying heterosexual experience or reducing pregnancies, drunkenness, or cannabis use. Some results suggested an adverse effect. Although methodological limitations may at least partly explain these findings, any further implementation of such interventions in the UK should be only within randomised trials.